“Efecto del lactosuero suministrado en forma líquida en dosis altas (30%,40% y 50%) en la crianza de pollos broilers en etapa de pollipavo (39 a 70 días)” - Gonzáles García, Jimmy Jheyson (2014)
This work is entitled "EFFECT OF WHEY SUPPLIED IN LIQUID FORM AT HIGH DOSES (30%, 40% and 50%)" IN THE BREEDING OF CHICKEN BROILERS (39 to 70 DAYS) POLLIPAVO STAGE) ".;" Likewise with the objective of evaluate the effect of the whey as supplement in power of chickens heavy for meat, supplied in form liquid, in three concentrations (30%, 40% and 50%) as water of drink in the stage of pollipavo (39 to 70 days); in the Region San Martin; is performed in the District of the band of Shilcayo, land of the center of production agricultural "Mirafloresn" Faculty of agricultural sciences of the National University of San Martin, located in the sector "Ahuashiyacu"; the area presents a precipitation average annual of 1200 mm / year. Average temperature of 26 ° C, maximum of 32 ° C and minima of 22 ° C; Likewise a relative humidity of 70%. It was used, the design completely at random (DCA), with 4 treatments and 2 replications. The results showed that you generated greater benefit...